Insights into the structure-induced catalysis dependence of simply engineered one-dimensional zinc oxide nanocrystals towards photocatalytic water purification. Issue 12 (2nd November 2017) - Xiong, Jinyan; Gan, Yixin; Zhu, Jiaxin; Li, Wei; Gao, Chao; Wei, Yi; Cheng, Gang; Li, Zhen; Dou, Shixue
Abstract : One-dimensional nanocrystalline semiconductors have been comprehensively studied because of their fascinating properties and practical applications in various fields. Abstract : One-dimensional nanocrystalline semiconductors have been comprehensively studied because of their fascinating properties and practical applications in various fields. However, exploring a facile preparation technique and improving and optimizing current performance remain big challenges. In this work, zinc oxide (ZnO) nanocrystals with different one-dimensional structures, ranging from multi-armed nanorods and rough nanorods to nanowires, have been successfully synthesized via a facile solvothermal strategy in a hexalene glycol–H2 O reaction system. The variations in the crystal phase and the structure of the ZnO nanocrystals are investigated in detail by using powder X-ray diffraction, scanning electron microscopy, and transmission electron microscopy. The effects of different ZnO structures on the catalytic ability were evaluated through the photodegradation of an antibiotic, ciprofloxacin, and an organic dye, Rhodamine B, under simulated solar light irradiation. The photocatalysis system constructed from the multi-armed ZnO nanorod photocatalyst shows superior efficiency compared to the ZnO nanorods and nanowires. This enhancement in the photocatalytic ability of the ZnO multi-armed nanorods compared to other nanostructures is attributed mainly to their unique structure, efficient electron–hole separation, and faster charge transport, on the basis of photoluminescence spectra, and photocurrent, and electrochemical impedance spectroscopy measurements.